(untitled) (Revista Científica Compendium, 2018)
Accidents at work and occupational diseases are the justification of the health systems. Preventive health is a priority. is article aims at a systematic review of the legal and technical aspects in occupational safety and health matters in the Republic of Ecuador. e objective is the designing of an Occupational Health and Safety Management System for higher education centers in the Province of Manabí. That is in order to prevent the occupational accidents and diseases, which consists of four phases: 1) diagnosis of the current situation regarding occupational safety and health, 2) identification and assessment of risk factors, 3) elaboration of the legal technical requirements applicable to the administrative, technical and human-talent management, and basic operational procedures and programs; and 4) assessment of the effectiveness of the improvements in occupational safety and health conditions. The systematic review of legal and technical aspects and procedures in occupational safety and health matters in the Republic of Ecuador would contribute to the proposal of diagnostic instruments and methodological indications in order to achieve the four phases mentioned previously.